Endodontic characteristics of mandibular premolar with dens evaginatus: a retrospective study - Minjin Kim; Sujin Jeon; Min-Seock Seo (Restorative Dentistry & Endodontics, 2024)
ObjectivesThis study aimed to investigate the endodontic characteristics of mandibular premolars with dens evaginatus (DE) that require endodontic treatment.Materials and MethodsPatients who underwent endodontic treatment were enrolled. The inclusion criteria were patients who underwent root canal treatment in the lower permanent teeth with DE and were followed up for at least 1 year. Preoperative clinical and radiographic variables were obtained. The frequency distribution of the preoperative variables was compared using the χ2 or Fisher’s exact tests. The significance of the change in periapical health index (PAI) and root development stages before and after treatment was examined using the Wilcoxon signed-rank test.ResultsA total of 150 teeth of 134 patients with an average age of 15.3 years were included. The percentage distribution comparison of the preoperative variables and obturation techniques revealed significant differences in pulpal and periapical diagnosis, and percussion, and especially regarding age, root development stage, and PAI. Age was the only statistically significant preoperative variable associated with root growth (p < 0.05).ConclusionsApproximately, 60% of DEs requiring endodontic treatment had immature roots. Age being the most significant predisposing factor, early treatment provides the greatest opportunity for full root development.